2020
DOI: 10.1111/bju.15042
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy reduces biochemical recurrence after radical prostatectomy

Abstract: Objective To evaluate risk of prostate cancer biochemical recurrence (BCR) after radical prostatectomy (RP) in men receiving vs not receiving testosterone replacement therapy (TRT). Patients and Methods A total of 850 patients underwent RP by a single surgeon. All patients had preoperative testosterone and sex hormone‐binding globulin levels determined; free testosterone was calculated prospectively. In all, 152 (18%) patients with low preoperative calculated free testosterone (cFT) levels and delayed postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 35 publications
1
17
0
2
Order By: Relevance
“…17 In a study of 850 men who underwent radical prostatectomy, Ahlering et al recently reported a lower biochemical recurrence rate (7.2%) among 152 men who received postoperative TTh compared with 419 proportionately matched controls who did not receive TTh (12.6%). 18 The most intriguing evidence for a possible role for TTh in men with mPCa comes from the BAT trials involving rapidly cycling supraphysiological and castrate levels of serum T. These landmark trials demonstrated 50% or greater declines in PSA in 7 of 14 evaluable men with castrate-resistant mPCa and radiographic responses in 5 of 10 evaluable cases. 15 A subsequent trial also re-established androgen sensitivity in men with CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a study of 850 men who underwent radical prostatectomy, Ahlering et al recently reported a lower biochemical recurrence rate (7.2%) among 152 men who received postoperative TTh compared with 419 proportionately matched controls who did not receive TTh (12.6%). 18 The most intriguing evidence for a possible role for TTh in men with mPCa comes from the BAT trials involving rapidly cycling supraphysiological and castrate levels of serum T. These landmark trials demonstrated 50% or greater declines in PSA in 7 of 14 evaluable men with castrate-resistant mPCa and radiographic responses in 5 of 10 evaluable cases. 15 A subsequent trial also re-established androgen sensitivity in men with CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…After accounting for the Gleason grade (GG) group, pathological stage, preoperative PSA level, and calculated free T, the authors determined that patients prescribed TRT were *54% less likely to recur (HR 0.54, 95% CI 0.292-0.997). 51 Among those men who would eventually recur, TRT appeared to delay time to recurrence by an average of 1.5 years. Importantly, this study reported that by 2 years post-RP, 96% of patients had re-gained erectile function.…”
Section: Trt In Patients With Treated Pcamentioning
confidence: 99%
“…An important limitation of this study was that younger men were included, unlike the PLCO and ERSPC trials. 28 In a case-control study in the United States, using a Surveillance, Epidemiology and End Results (SEER) Medicare-linked database, patients with a diagnosis of PCa and with history of T use (574 men) were compared with PCa patients without history of T use (51,945). Those patients who had received TRT in the 5 years before diagnosis were found not to have an increased risk of high-grade disease at diagnosis (odds ratio [OR] 0.84, 95% CI 0.67-1.05).…”
Section: Trt and Risk Of Developing Pcamentioning
confidence: 99%
“…Ahlering T, et a.l, 4 answered the question with their study in 2020, in which 152 men with low testosterone, post-radical prostatectomy treated with TT were compared with 419 controls with a normal testosterone post-op. The median follow-up was 3.5 years.…”
Section: Messages For the Clinicmentioning
confidence: 99%